Which indicators of absorptive capacity enhance import-induced South-North convergence in labor intensities? - Michael Hübler; Alexander Glas (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We hypothesize that North-South trade is associated with knowledge spillovers that create labor productivity gains depending on various determinants of Southern absorptive capacity. We use the novel World Input-Output Database (WIOD) that provides bilateral and bisectoral panel data for 39 countries and 35 sectors for 1995-2009. We examine growth in relative South-North labor intensities (South-North convergence) for 31 industrialized source and eight emerging recipient countries. We find robust evidence that the following measures of absorptive capacity (ordered by magnitude of the estimated coefficients) interact with imports so that relative labor intensity is reduced: economic freedom and political and civil rights, services, skills, scientific publications and patents as well as telephone and internet access. GMM and GLS estimations corroborate the results. Policies that support various of the identified determinants of absorptive capacity are more promising than policies that select only one. Elevating the absorptive capacity of emerging economies to the maximum level in the world would halve the South-North gap in labor intensities within a couple of decades if it were solely achieved through the trade channel.
Keywords: C23; F18; F21; O13; O33; O47; Q43; 330; absorptive capacity; labor intensity; trade; South-North; convergence